REVITALIZING SECONDARY SCHOOLS THROUGH ENTREPRENEURSHIP EDUCATION IN NIGERIA - Amaechina, Uche Obumneme; Alaubi, Stanley C. (UNIZIK Journal of Educational Management and Policy, 2018)
Entrepreneurship education in Nigeria seeks to provide students at all level of education with the knowledge, skills and motivation to encourage entrepreneurial success in a variety of ventures. This paper focused on revitalizing secondary schools through entrepreneurship education. It highlighted the concepts of entrepreneurship education, entrepreneurship education in secondary schools and challenges of entrepreneurship education in Nigeria. The paper concluded that, entrepreneurship education is a central pillar to economic growth and development, as well as employment generation and poverty alleviation which has not been fully embraced and functional in Nigeria. Recommendations were made which include that: students should be trained very well in the area of technology and computer manipulation for a genuine business online, entrepreneurship education should be introduced in the schools right from primary, through secondary and to tertiary institutions and that the government should ensure that the curriculum of secondary education is strengthened to accommodate more business and vocational courses and training.